Early infancy‐onset stimulation‐induced myoclonic seizures in three siblings with inherited glycosylphosphatidylinositol (GPI) anchor deficiency. Issue 1 (6th March 2018) - Mogami, Yukiko; Suzuki, Yasuhiro; Murakami, Yoshiko; Ikeda, Tae; Kimura, Sadami; Yanagihara, Keiko; Okamoto, Nobuhiko; Kinoshita, Taroh
ABSTRACT: Inherited glycosylphosphatidylinositol anchor deficiency causes a variety of clinical symptoms, including epilepsy, however, little information is available regarding seizures as a symptom. We report three siblings with inherited glycosylphosphatidylinositol anchor deficiency with PIGL gene mutations. The phenotypes of the subjects were not consistent with CHIME syndrome or Mabry syndrome, as reported in previous studies. All shared some clinical manifestations, including transient apnoea as neonates, dysmorphic facial features, and intellectual disability. Between one week and 3 months of life, all patients developed myoclonic seizures. Myoclonic jerks were easily evoked by sudden unexpected acoustic or tactile stimuli. None showed elevation of serum alkaline phosphatase. Vitamin B6 was given to one of the three siblings, but failed to suppress seizures. The presence of early infancy‐onset stimulation‐induced myoclonic seizures combined with dysmorphic facial features should lead physicians to consider the possibility of inherited glycosylphosphatidylinositol anchor deficiency.